Methionine and cysteine oxidation are regulated in a dose dependent manner by dietary Cys intake in neonatal piglets receiving enteral nutrition. - Anna K Shoveller; Julia G Pezzali; James D House; Robert F Bertolo; Paul B Pencharz; Ronald O Ball (PLoS ONE, 2022)
Methionine (Met) is an indispensable amino acid (AA) in piglets. Met can synthesize cysteine (Cys), and Cys has the ability to reduce the Met requirement by 40% in piglets. However, whether this sparing effect on Met is facilitated by downregulation of Cys synthesis has not been shown. This study investigated the effects of graded levels of Cys on Met and Cys oxidation, and on plasma AA concentrations. Piglets (n = 32) received a complete elemental diet via gastric catheters prior to being randomly assigned to one of the eight dietary Cys levels (0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.40, 0.50 g kg-1d-1) with an adequate Met concentration (0.25g kg-1d-1). Constant infusion of L-[1-14C]-Met and L-[1-14C]-Cys were performed for 6 h on d 6 and d 8 to determine Met and Cys oxidation, respectively. Met oxidation decreased as Cys intake increased (P<0.05). At higher Cys intakes (0.15 to 0.5g kg-1d-1), Met oxidation decreased (P<0.05) at a slower rate. Cys oxidation was similar (P>0.05) among dietary Cys intakes; however, a significant polynomial relationship was observed between Cys oxidation and intake (P<0.05, R2 = 0.12). Plasma Met concentrations increased (P<0.05) linearly with increasing levels of dietary Cys, while plasma Cys concentrations changed (P<0.05) in a cubic manner and the highest concentrations occurred at the highest intake levels. Increasing dietary levels of Cys resulted in a reduction in Met oxidation until the requirement for the total sulfur AA was met, indicating the sparing capacity by Cys of Met occurs through inhibition of the transsulfuration pathway in neonatal piglets.